The 'Everything But Thesis' Syndrome at the Postgraduate Level: A Case Study of Academic Factors Affecting the Final Graduation Project Elaboration Process - Mena Rojas, Warner Arturo (2024)
The study highlights the importance of research and institutional evaluation as fundamental strategies to address issues affecting higher education. Specifically, it focuses on the low graduation rates faced by some postgraduate programs and addresses the "everything but the thesis syndrome," a recurring phenomenon in which the student population successfully completes the curriculum but fails to finish the final graduation project for various reasons. Since this syndrome is considered one of the main causes of low graduation rates in postgraduate programs, the study conducts a literature review to identify theoretical references. Through this process, twenty-four academic factors that can positively or negatively influence the completion of the final graduation project are identified. To obtain specific data, a survey is administered to the graduating population of two cohorts from an international postgraduate program at the National University of Costa Rica. Using a Likert scale, the factors that, according to the perception of the surveyed individuals, have the greatest positive or negative impact on the final graduation project development process are determined. "Knowledge and familiarity with the research topic" are positively highlighted, while the "transition process from the project proposal to the final project" is viewed negatively. In addition to the survey, the historical records of the postgraduate program are reconstructed, and the program's efficiency rate is calculated, along with other relevant indicators for analysis.